Facile preparation of amorphous cobalt phosphate as inorganic carrier for direct separation and immobilization of his-tagged β-glucosidase from cell lysate. (2nd November 2022) - Ma, Xinnan; Chen, Zhili; Han, Juan; Zhou, Yang; Mao, Yanli; Li, Chunmei; Wang, Lei; Wang, Yun
Abstract : The present work was aimed to develop a facile method to fabricate solid support for the separation and immobilization of his-tagged enzymes directly from cell lysate without pre-purification of the enzymes. Abstract : The present work was aimed to develop a facile method to fabricate solid support for the separation and immobilization of his-tagged enzymes directly from cell lysate without pre-purification of the enzymes. Cobalt phosphate with different morphology and structure was simply fabricated by regulating the Co 2+ concentration, and it was employed as inorganic carrier for the direct separation and immobilization of his-tagged β-glucosidase (GLH) from cell lysate via coordination interaction between Co 2+ and the his-tag. The morphology and structure of Co3 (PO4 )2 @GLH were confirmed by FT-IR, DLS, TGA, CLSM, SEM, EDS, and TEM. The amorphous cobalt phosphate aggregated by lamellae showed unique advantages for enzyme immobilization. The resultant Co3 (PO4 )2 @GLH prepared under optimum conditions exhibited a high activity recovery (82.1%), relative activity (1.1) and specific enzyme activity (7887.1 U g −1 ), with enhanced storage stability and recyclability. The immobilized GLH was able to retain ∼72% activity after eight cycles. The results indicate that the amorphous cobalt phosphate material could be an excellent candidate for the separation and immobilization of his-tagged enzyme directly from cell lysate.